Optimalisasi Project Based Learning melalui Penggunaan Media Canva Oleh Guru Biologi Yayasan Pendidikan Firdaus Maros - Pertiwi Indah Lestari; Nur Arif MS; Wahyuni; Abdul Hakim; Farida Febriati (Lembaga Bale Literasi, 2026)
This study aims to describe the optimization of the Project Based Learning (PjBL) model through the use of Canva media in Biology learning at the Firdaus Maros Education Foundation. This study uses a qualitative descriptive approach with data collection techniques through in-depth interviews with four Biology teachers. The results show that the use of Canva can improve the quality of learning through the presentation of materials that are more visual, interactive, and interesting. The integration of Canva in project-based learning encourages active student engagement, increases learning motivation, and develops 21st-century skills such as critical thinking, creativity, collaboration, and communication. Students not only understand Biology concepts theoretically, but are also able to produce tangible products such as posters, infographics, and presentations as a form of their understanding. Despite obstacles such as limited internet connection and variations in digital literacy, the use of video tutorials and support from belajar.id accounts are solutions in optimizing the use of Canva. Thus, Canva plays a role not only as a learning medium, but also as a strategic tool in supporting the implementation of Project Based Learning that is innovative and relevant to the demands of 21st-century learning.